2001
DOI: 10.1186/bcr294
|View full text |Cite
|
Sign up to set email alerts
|

Allelic loss on chromosome band 18p11.3 occurs early and reveals heterogeneity in breast cancer progression

Abstract: DCIS = ductal carcinoma in situ; IDC = invasive ductal carcinoma; LOH = loss of heterozygosity; PCR = polymerase chain reaction. AbstractWe examined the stage specificity and heterogeneity of 18p11 alterations in a series of tumors representing 96 microdissected samples. Significant loss of heterozygosity (LOH) (63%) was found, with 56% occurring early in ductal carcinoma in situ. Although most cases indicated LOH was clonally inherited, heterogeneity for 18p LOH occurred in 27% of tumors. When compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 19 publications
(28 reference statements)
0
34
0
Order By: Relevance
“…Loss of the 18p chromosomal region has been shown as an early event in breast cancer progression [35] and has been associated with a poor outcome [7]. Addou-Klouche et al…”
Section: Discussionmentioning
confidence: 99%
“…Loss of the 18p chromosomal region has been shown as an early event in breast cancer progression [35] and has been associated with a poor outcome [7]. Addou-Klouche et al…”
Section: Discussionmentioning
confidence: 99%
“…Loss of heterozygosity at multiple loci has been reported to occur early in tumorigenesis in a number of cancers (Watson et al 1998;Lakhani et al 1999;Kittiniyom et al 2001). Assessment of metastatic potential will be another exciting application, as demonstrated by the recent findings that gene-dosage increases for PRL3 at 8q24.3 correlate with metastasis in colon cancer (Saha et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that protein 4.1B may function as a tumor suppressor protein whose expression is lost in breast cancers (Tran et al, 1998;Kittiniyom et al, 2001;Charboneau et al, 2002). However, the role of 4.1B in normal mammary epithelium had not been previously tested.…”
Section: Protein 41b Expression Is Induced In Mammary Epithelia Durimentioning
confidence: 99%
“…Because loss of this region occurs with relatively high frequency in ductal carcinomas in situ (56%), it has been proposed to be an early event in tumor progression in the breast (Kittiniyom et al, 2001). Furthermore, re-introduction of the minimal growth inhibitory domain of 4.1B, called DAL-1 (differentially expressed in adenocarcinoma of the lung), results in growth suppression in a number of mammary carcinoma cell lines (Charboneau et al, 2002).…”
Section: Introductionmentioning
confidence: 99%